Medical Imaging and Informatics - Gao, X. (Springer, 2017)
This book constitutes the thoroughly refeered post-conference proceedings of the Second Interational Conference on Medical Imaging and Informatics, MIMI 2007, held in Beijing, China, in August 2007.